Consumer Preferences Towards Broiler Chicken Supplemented With Nanoencapsulated Liquid Turmeric Extract in Drinking Water - Hidayat, Muhammad; Zuprizal, Zuprizal; Sundari, Sundari; Kusmayadi, Andri; Wati, Ari Kusuma (ANIMAL PRODUCTION, 2018)
The purpose of this research was to investigate the effects of nanoencapsulation liquid turmeric extract (NLTE) supplementation as a phytobiotic on organoleptic quality of broiler chicken meat. The research was conducted with a directional pattern completely randomized design. Eighty-four broiler chickens were raised from day old (DOC) to 42 days old chick. From DOC to 14 days old, chicks were fed with commercial feed (ME 3,100 kcal/kg; CP 22%; Ca 1%; P 0.75%). During 15-21 days of age, chicks were given a mixture commercial feed and basalt feed (ME 3,201.77 kcal/kg; CP 20.21%; Ca 0.90%; and P 0.43%). At 22-42 days old, they were given treatments by basal feeding. Seven treatments were replicated 3 times consisted of 4 broiler chickens for each replication. The treatments were positive control (P1), negative control (P2), water + NLTE 2% (P3), water + NLTE 4% (P4), water + NLTE 6% (P5), water + NLTE 8% (P6), and water + NLTE 10% (P7). The results showed that supplementation NLTE significantly increased (P<0.05) the taste of broiler meat. However, it did not show a significant influence (P>0.05) on the texture, colour, tenderness, and preference of meat.